Non-linear Association Between Body Mass Index and Ventricular Tachycardia/Ventricular Fibrillation in Patients With an Implantable Cardioverter-Defibrillator or Cardiac Resynchronization Therapy Defibrillator: A Multicenter Cohort Study - Zhou, Bin; Zhao, Shuang; Tang, Min; Chen, Keping; Hua, Wei; Su, Yangang; Yang, Jiefu; Liang, Zhaoguang; Xu, Wei; Zhang, Shu (Frontiers in Cardiovascular Medicine, 2020)
Abstract Background: Results from studies on the effects of obesity on sudden cardiac death (SCD) or ventricular tachycardia/ventricular fibrillation (VT/VF) in patients with an implantable cardioverter-defibrillator/cardiac resynchronization therapy defibrillator (ICD/CRT-D) are inconsistent. Our study aimed to explore the impact of BMI on VT/VF in patients with an ICD/CRT-D. Methods: We retrospectively analyzed the data from the Study of Home Monitoring System Safety and Efﬁcacy in Cardiac Implantable Electronic Device–implanted Patients in China. Nine hundred and seventy ICD/CRT-D patients were enrolled. The outcome was the first occurrence of VT/VF requiring appropriate ICD/CRT-D therapy. A general linear model and general additive model were used to assess the relationship between BMI and VT/VF. Results: After a median follow-up of 5.17 years, 352 (36.3%) patients experienced VT/VF requiring appropriate ICD/CRT-D therapy. BMI, whether as a continuous variable or a categorical variable classified by various BMI classification criteria, had no significant effect on VT/VF according to a multivariable Cox proportional hazards model with adjustment for potential confounders. However, a nonlinear association between BMI and VT/VF was identified using a cubic spline function model and smooth curve fitting. The inﬂection point for the curve was found at a BMI level of 23 kg/m2. The hazard ratios (95% conﬁdence intervals) for VT/VF were 1.12 (1.01-1.24) and 0.96 (0.90 -1.02) to the left and right of the inﬂection point, respectively. Conclusions: BMI is related to VT/VF in a nonlinear manner in patients with an ICD/CRT-D. Our research suggests a complicated role of BMI in VT/VF with different impacts at different ranges.